2023
DOI: 10.32471/exp-oncology.2312-8852.vol-42-no-2.14579
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of androgen receptor expression in patients with metastatic triple negative breast cancer

Abstract: Summary. At present, there are no valid prognostic biomarkers in patients with triple negative breast cancer (TNBC) except well known clinical factors such as tumor size, lymph node status, differentiation grade and proliferation rate. Aim: To evaluate the prognostic role of androgen receptor (AR) expression in patients with TNBC. Materials and Methods: The effect of the AR expression level in tumor tissue on overall survival depending on clinical, histological and immunohistochemical characteristics of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
10
1
1
Order By: Relevance
“…It has been observed that AR negative TNBCs are more likely to have lymph node metastases than AR positive tumors. 33 , 38 , 39 In addition, multiple studies find that AR negative tumors are more likely to present at a higher grade and stage than AR positive tumors. 29 , 30 , 34 , 35 , 37 From the limited research on TNBC histological subtypes, IDC is the most common, with one paper presenting that AR negative tumors are more likely to be ductal than AR positive tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that AR negative TNBCs are more likely to have lymph node metastases than AR positive tumors. 33 , 38 , 39 In addition, multiple studies find that AR negative tumors are more likely to present at a higher grade and stage than AR positive tumors. 29 , 30 , 34 , 35 , 37 From the limited research on TNBC histological subtypes, IDC is the most common, with one paper presenting that AR negative tumors are more likely to be ductal than AR positive tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 34 , 36 , 41 This includes a better OS time after three and five years for patients with AR+ tumors than AR- tumors. 37 , 38 , 41 Appendix C compares the OS times of TNBC patients from different studies. However, these studies do not examine whether patient treatment choices affected their respective survival times.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, AR expression in TNBC was associated with longer DFS and OS [ 35 ]. In a study based on 116 metastatic TNBC cases, AR positive expression was found to be an independent prognostic protective factor, as AR positivity (AR > 10%) was associated with higher 5-year survival [ 14 ]. However, in a study of 263 patients with primary early TNBC, AR expression and its correlation with prognosis was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies reporting prognostic implications of AR expression in TNBC and HER2 positive subtypes had paradoxical results. Some studies indicated AR positivity was associated with a better outcome [ 14 16 ], others reported a worse prognosis [ 17 19 ]. Moreover, it also has been reported that there was no correlation between AR status and outcome in TNBC [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Las líneas celulares de CMTN positivos al AR a menudo expresan mutaciones de PI3KCA, volviéndolos más sensibles a los inhibidores de PI3K/mTOR. Es importante destacar que los AR en el CMTN interactúan con la poli(ADPribosa) polimerasa 1 (PARP1) y BRCA1, reguladores del ciclo celular BRCA1 y PARP1 activan la transcripción de genes AR estimulando el crecimiento tumoral (Leung y Sadar, 2017;Lyalkin et al, 2020).…”
Section: Andrógenos Estructura Y Función De Los Andrógenosunclassified